The Factors of Economic Mechanism for Recovery the Domestic Market of Donbas - Kolosov, A.M. (Економічний вісник Донбасу, 2015)
The comparative analysis of the economic indicators of the European Union, Ukraine and the Donbas as part of it. It is shown that an increase in the level of wages, the wage share in the cost of production, the share of the domestic market in total sales, small business development in Ukraine and Donbas are possible only on the basis of significant European investment, but not only in the export enterprises, but also in the development of the internal market for the production of domestic consumption. It must inevitably be a factor in the progressive increase in wages and other incomes. The central point of the launch of this mechanism, excluding inflation, is to provide a dynamic balance between the volume coming to the domestic market additional products and an inic consumption.